2021
DOI: 10.3390/children8070534
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Interventions for Treatment of Neonatal Opioid Withdrawal Syndrome: A Review

Abstract: This study assessed the economic evidence on the pharmacological and non-pharmacological management of infants with neonatal opioid withdrawal syndrome (NOWS). Six databases were searched up to October 2020 for peer-reviewed studies. After titles and abstracts were screened, 79 studies remained for full-text review, and finally, 8 studies were eligible for inclusion in the review. The methodological quality of included studies was assessed using the Drummond checklist. The review showed significant limitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“… Overview of the themes and specific papers discussed in this Special Issue [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… Overview of the themes and specific papers discussed in this Special Issue [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. …”
Section: Figurementioning
confidence: 99%
“…There is also a lack of evidence on long-term outcomes associated with NOWS and its treatment. The authors therefore concluded that inclusion of economic analyses in future studies is needed to provide evidence to inform policymakers on resource allocation decisions for this patient population [ 6 ]. Finally, Kim et al focused on preschool language development in NOWS children.…”
mentioning
confidence: 99%
“…The MAiN rooming-in program was safe, effective, and reduced costs by more than 50% when using non-critical care beds compared with NICU beds as the main cost driver [ 27 ]. Multiple studies corroborate these findings, identifying that nonpharmacological strategies such as rooming-in for NAS management compared to NICU care were associated with a shorter hospital LOS and a decreased need for pharmacological treatment, thereby lowering hospitalization costs [ 26 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 95%
“…2,8 The financial burden of NOWS on health care systems is significant, as costs associated with NOWS in Canadaincluding increased LOS and NICU-were estimated at $26.9 million in 2014. 14 This current standard of care in Canada to admit infants with NOWS to NICU with continuous cardiovascular monitoring when pharmacological treatment is required exacerbates economic burdens to the health care system, and can disrupt the mother-infant dyad, which is detrimental to the development of maternal attachment, and the length and severity of NOWS symptoms. 9,15 The aim of this quality assurance project at FIR was to ensure the safety of our standard practices of MOS treatment for infants diagnosed with NOWS outside of the NICU.…”
Section: Introductionmentioning
confidence: 99%